Increased tumorigenesis associated with loss of the tumor suppressor gene Cadm1 - van der Weyden, Louise (BioMed Central, 2012)
BACKGROUND: CADM1 encodes an immunoglobulin superfamily (IGSF) cell adhesion molecule. Inactivation of CADM1, either by promoter hypermethylation or loss of heterozygosity, has been reported in a wide variety of tumor types, thus it has been postulated as a tumor suppressor gene. FINDINGS: We show for the first time that Cadm1 homozygous null mice die significantly faster than wildtype controls due to the spontaneous development of tumors at an earlier age and an increased tumor incidence of predominantly lymphomas, but also some solid tumors. Tumorigenesis was accelerated after irradiation of Cadm1 mice, with the reduced latency in tumor formation suggesting there are genes that collaborate with loss of Cadm1 in tumorigenesis. To identify these co-operating genetic events, we performed a Sleeping Beauty transposon-mediated insertional mutagenesis screen in Cadm1 mice, and identified several common insertion sites (CIS) found specifically on a Cadm1-null background (and not wildtype background). CONCLUSION: We confirm that Cadm1 is indeed a bona fide tumor suppressor gene and provide new insights into genetic partners that co-operate in tumorigenesis when Cadm1-expression is lost.